The Effects of Gender Diversity in The Boardroom on Firm Financial Performance in Indonesia - Linggih, Ayu Denisa; Wiksuana, I G. B. (Jurnal Ekonomi Kuantitatif Terapan, 2018)
This research investigates the effects of gender diversity in the boardroom on firm financial performance in Indonesia. To achieve the objective of this study, panel data analysis and fixed effects estimators have been applied to companies listed in Indonesia Stock Exchange in 2014 until 2016.  The result of this study indicates that the percentage of women in the boardroom (board of commissioners and board of directors) has a significant positive effect on the company's financial performance as measured by return on assets (ROA). The relationship between these variables is then explained by agency theory where increasing the percentage of women in the boardroom improves the supervision of the company's agents which in return will positively affect the financial performance of the company. The managerial implications and suggestions of this research are that companies should begin to empower more women in the company's top management, also the government should consider a minimum quota policy for women on board of commissioners and directors in Indonesia.